Regulating Corporate Criminal Liability
XII, 360 p. 2 illus.
Keywords: Corporate Criminal Liability is on the rise worldwide: More and more legal systems now include genuinely criminal sanctioning for legal entities. The various regulatory options available to national criminal justice systems, their implications and their constitutional, economic and psychological parameters are key questions addressed in this volume. Specific emphasis is put on procedural questions relating to corporate criminal liability, on alternative sanctions such as blacklisting of corporations, on common corporate crimes and on questions of transnational criminal justice. .